Prevotella hominis sp. nov., isolated from human faeces. Issue 8 (22nd August 2020) - Liou, Jong-Shian; Huang, Chien-Hsun; Ikeyama, Nao; Lee, Ai-Yun; Chen, I-Ching; Blom, Jochen; Chen, Chih-Chieh; Chen, Chia-Hsuan; Lin, Yu-Chun; Hsieh, Sung-Yuan; Huang, Lina; Ohkuma, Moriya; et al.
Abstract : A strictly anaerobic predominant bacterium, designated as strain gm001 T, was isolated from a freshly voided faecal sample collected from a healthy Taiwanese adult. Cells were Gram-stain-negative rods, non-motile and non-spore-forming. Strain gm001 T was identified as a member of the genus Prevotella, and a comparison of 16S rRNA and hsp60 gene sequences revealed sequence similarities of 98.5 and 93.3 %, respectively, demonstrating that it was most closely related to the type strain of Prevotella copri . Phylogenomic tree analysis indicated that the gm001 T cluster is an independent lineage of P. copri DSM 18205 T . The average nucleotide identity, digital DNA‒DNA hybridization and average amino acid identity values between strain gm001 T and P. copri DSM 18205 T were 80.9, 28.6 and 83.8 %, respectively, which were clearly lower than the species delineation thresholds. The species-specific genes of this novel species were also identified on the basis of pan-genomic analysis. The predominant menaquinones were MK-11 and MK-12, and the predominant fatty acids were anteiso-C15 : 0, C15 : 0 and iso-C15 : 0 . Acetate and succinate were produced from glucose as metabolic end products. Taken together, the results indicate that strain gm001 T represents a novel species of the genus Prevotella, for which the name Prevotella hominis sp. nov. is proposed. The type strain is gm001 T (=BCRC 81118 T =JCM 33280 T ).